2014
DOI: 10.1371/journal.pone.0088452
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Subset Distributions in the Aorta in Healthy and Atherosclerotic Mice

Abstract: Dendritic cells (DCs) can be sub-divided into various subsets that play specialized roles in priming of adaptive immune responses. Atherosclerosis is regarded as a chronic inflammatory disease of the vessel wall and DCs can be found in non-inflamed and diseased arteries. We here performed a systematic analyses of DCs subsets during atherogenesis. Our data indicate that distinct DC subsets can be localized in the vessel wall. In C57BL/6 and low density lipoprotein receptor-deficient (Ldlr −/−) mice, CD11c+ MHCI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 28 publications
0
24
0
Order By: Relevance
“…The loss of CD103 + and of some CD11b + cDCs in the nonatherosclerotic aorta in Flt3/Flt3l-deficient mice 4,14 indicates that monocyte-derived DCs and bone fide cDCs are already present prior disease development. Whereas blood monocytes systemically increase, 34 it is unclear whether circulating DCs or their precursors are altered in hyperlipidemia.…”
Section: Trafficking Of Dcsmentioning
confidence: 99%
“…The loss of CD103 + and of some CD11b + cDCs in the nonatherosclerotic aorta in Flt3/Flt3l-deficient mice 4,14 indicates that monocyte-derived DCs and bone fide cDCs are already present prior disease development. Whereas blood monocytes systemically increase, 34 it is unclear whether circulating DCs or their precursors are altered in hyperlipidemia.…”
Section: Trafficking Of Dcsmentioning
confidence: 99%
“…No differences in pDCs were noted (0.37% ± 0.08% versus 0.32% ± 0.03% CD11c low/+ Siglec H + cells among CD45 + cellls in Ldlr -/- versus Ldlr -/- Batf3 -/- mice, respectively). CD103 + DCs can be found within the aortic sinus of chow-fed animals where they represent up to 20% of total DCs [ 14 , 23 ]. As expected, CD103 + APC were completely absent in cell suspensions prepared from the aortic sinus of Ldlr -/- Batf3 -/- mice compared to control Ldlr -/- animals, whereas a relative increase in CD11b + APCs were observed (Panel C in S1 Fig ).…”
Section: Resultsmentioning
confidence: 99%
“…in the intestinal mucosa [ 29 , 30 ]. However, Flt3 is not only expressed in this DC subset but is also present in other CD11c + MHCII + DC subsets, and we have previously shown that deficiency in its ligand in Flt3 -/- mice for example resulted not only in a loss of CD103 + DCs in the aorta, but in addition was associated with a marked reduction in CD11b + DCs [ 23 ]. Flt3 can also be found on some natural killer (NKs) cells [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous research revealed that DCs accumulate in atherosclerotic lesions (38) and are predisposed to atherosclerosis, which is a well-known, chronic inflammatory disease of the large and medium arteries (39). We then concentrated on the migration ability of DCs in ApoE 2/2 mice and demonstrated an unexpected change in DCs, which could be hidden by traditional bulk-cell analysis.…”
Section: Discussionmentioning
confidence: 96%